Evaluating the cerebral correlates of survival in amyotrophic lateral sclerosis. Issue 11 (23rd September 2018) - Ishaque, Abdullah; Mah, Dennell; Seres, Peter; Luk, Collin; Eurich, Dean; Johnston, Wendy; Yang, Yee‐Hong; Kalra, Sanjay
Abstract: Objective: To evaluate cerebral degenerative changes in ALS and their correlates with survival using 3D texture analysis. Methods: A total of 157 participants were included in this analysis from four neuroimaging studies. Voxel‐wise texture analysis on T1‐weighted brain magnetic resonance images (MRIs) was conducted between patients and controls. Patients were divided into long‐ and short‐survivors using the median survival of the cohort. Neuroanatomical differences between the two survival groups were also investigated. Results: Whole‐brain analysis revealed significant changes in image texture (FDR P  <   0.05) bilaterally in the motor cortex, corticospinal tract (CST), insula, basal ganglia, hippocampus, and frontal regions including subcortical white matter. The texture of the CST correlated ( P  <   0.05) with finger‐ and foot‐tapping rate, measures of upper motor neuron function. Patients with a survival below the media of 19.5 months demonstrated texture change (FDR P  <   0.05) in the motor cortex, CST, basal ganglia, and the hippocampus, a distribution which corresponds to stage 4 of the distribution TDP‐43 pathology in ALS. Patients with longer survival exhibited texture changes restricted to motor regions, including the motor cortex and the CST. Interpretation: Widespread gray and white matter pathology is evident in ALS, as revealed by texture analysis of conventional T1‐weighted MRI. Length of survival in patients with ALS is associated with the spatial extent of cerebral degeneration.